Rethinking 'supply and demand' of technical and vocational education and training: insights from a company survey in three manufacturing sectors in South Africa. Issue 5 (18th August 2021) - Allais, Stephanie; Schoer, Volker; Marock, Carmel; Kgalema, Victor; Ramulongo, Nduvho; Sibiya, Tolika
ABSTRACT: This paper presents the results of a company survey focused on the role of technical and vocational education and training (TVET) in industrial transformation and growth in three manufacturing sectors in South Africa. We find two main patterns from our data: Those companies that take training seriously do this in a comprehensive way and reflect on this training as a combination of formal, informal, and on-the-job training. Second, the industries in which the majority of companies report use of TVET qualifications for hiring and in-house training are those in which training is integral to industrial strategy pertaining to new technologies, work-organisation, and products rather than as an adjunct to these core industry imperatives. These patterns have implications for policy, which tends in South Africa, like many countries, to be strongly focused on formal TVET provision, with little consideration of the broader picture of training, and with little sectoral specificity and little integration into economic development strategies. This also has implications for research into TVET, which, especially in the African context, has tended to look at formal provision on its own rather than as one component of a broader set of vocational skills development interventions.